Konstribusi Pembiayaan Perbankan Syariah Terhadap Pengembangan Usaha Mikro Kecil Dan Menengah (UMKM) Di Kota Makasar - Muslimin Kara (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
The Characteristic of Islamic banking is different with Conventional bank in terms of interest system in which Islamic banking is based on core product in sharing profit such as musy?rakahand mu??rabah. It is therefore the existence of Islamic banking should have a significant impact on real sector development. One of a such real factor that must be established is small and medium Micro Finance (UMKM) where has significant contribution in national economic development for employment recruitment and Domestic Bruto Income (PDB) as well as its stability in encountering economic crisis. The Islamic banking allocation for UMKM in Makassar has flucktuative improvement (2010-2011). Although its contribution for Micro Finance is not yet optimum, it has great prospects with respect to the quality of UMKM that never receives budgets.